Statistical study of frictional wind veering in the planetary boundary layer - Mendenhall, Bruce R., author (Colorado State University. Libraries, 1967)
Despite the general applicability of classical Ekman theory, individual observations of wind veering in the planetary boundary layer seldom exhibit the typical spiral turning with height. This study attempts to assess the reasons for these deviations from theory which occur not only as large fluctuations in time but also as significant differences in mean profiles from one location to another. The magnitude of the short-term eddy fluctuations is large in comparison to average frictional veering. A statistical analysis of sufficiently long periods of observational data is made in order to eliminate these small-scale variations. An assessment of the large-scale veering parameters is then possible. Wind tower and conventional rawinsonde veering data of three to five year periods from various land and ocean stations are objectively analyzed. Average wind profiles and statistics of the individual observations in the lowest two kilometers are computed in order to determine which parameters significantly affect frictional wind veering. Corrections to observed veering are made for the horizontal temperature gradient (rotation of the pressure gradient with height) and for variations of thermal stability. The relative importance of these corrections and the nature of their variability in different climatic regions are discussed. After statistically eliminating the unsteady effects and applying corrections for horizontal and vertical temperature gradients, a more realistic spiral is obtained at each station.
December 1967.
Also issued as author's thesis (M.S.) -- Colorado State University, 1967.
Keywords: Time-series analysis; Winds -- Measurement; Boundary layer